ANALISIS STRATEGI KERAGAMAN PRODUK OLAHAN MIE DALAM MENINGKATKAN OMZET PENJUALAN PADA KEDAI MIE JEMBER - Yudi Al Amin; Sutrisno Djaja (Economic Education, University of Jember, 2015)
This research was conducted to find out the application of the strategy of diversity products used in Kedai Mie Jember in increasing its sales volume. This research was conducted in Jalan Sumatra No. 126 Jember. The purpose of this study was to describe the application of diversity strategy products processed noodles in increasing sales volume in Kedai Mie Jember. Type of this research is a descriptive qualitative research. The determination of the location of research using the method of purposive area in Kedai Mie Jember. Data collection by the method of observation, interview and documentation. The results showed that the strategy of diversity related products rated effective increase sales volume in Kedai Mie Jember. It is reflected in the data on average sales volume of the acquired Kedai Mie Jember on semester 1 Manager of Kedai Mie Jember after applying on the diversity strategy prepared noodles produced increased by Rp 53.070.833,- per month with 35.80% percentage. While the average sales volume of the acquired Kedai Mie Jember on semester 2 after the Manager of Kedai Mie Jember on the diversity strategy prepared noodles produced amounted to Rp 55.264.833,- per month with the percentage of 41.32%. The increase sales volume of the acquired Kedai Mie Jember on semester 2 average is larger when compared with the sales volume of the acquired Kedai Mie Jember in semester 1.